Simvastatin reduces MMP-3 level in interleukin 1β stimulated human chondrocyte culture. Issue 7 (11th June 2004) - Lazzerini, P E; Capecchi, P L; Nerucci, F; Fioravanti, A; Chellini, F; Piccini, M; Bisogno, S; Marcolongo, R; Laghi Pasini, F
Abstract : Objectives: Matrix metalloproteinases (MMPs) produced by chondrocytes play a role in the development of cartilage degradation in joint diseases. Moreover, inhibition of MMP secretion by macrophages accumulating in arteriosclerotic plaques would account for the plaque stabilising activity of statins in cardiovascular patients. Recently, simvastatin has been shown to inhibit both developing and established collagen induced arthritis in a murine model. We thus decided to investigate the effect of simvastatin on the production of MMP-3 from cultured interleukin (IL)1 stimulated human chondrocytes. Methods: Cells from human cartilage, obtained from eight subjects with osteoarthritis undergoing surgery for total hip prostheses, were cultured in the presence of different concentrations of simvastatin (5, 10, and 50 μmol/l) with and without IL1β (5 ng/ml). MMP-3 level was measured in the culture medium after 48 h of incubation. Results: IL1β stimulation of chondrocytes increased MMP-3 concentration in the cultures (from 0.69 (0.09) to 1.94 (0.12) ng/μg protein). Incubation with simvastatin was associated with a dose dependent reduction in MMP-3 increase, both in the presence (−15%, −17%, and −26% with 5, 10, and 50 μmol/l, respectively) and in the absence (−32% with 50 μmol/l) of IL1β. The inhibiting effect of simvastatin was completely reversed by the addition of mevalonate (100 μmol/l) or farnesol (10 μmol/l). Conclusions: Our data show that simvastatin, by blocking HMGCoA-reductase and interfering in the prenylation processes, is able to inhibit MMP-3 production from cultured human chondrocytes that have been either unstimulated or stimulated with IL1β, thus suggesting a possible additional mechanism for statins in counteracting chronic joint disease related cartilage damage.